2020
DOI: 10.14246/irspsd.8.1_59
|View full text |Cite
|
Sign up to set email alerts
|

On the Applicability of a Western Bikeability Index in the Chinese Context

Abstract: Following the evolutionary pattern already observed in western countries, China is now witnessing a tremendous growth in car ownership that is reshaping the urban environment. Despite the surge in motorised traffic, the remaining high level of bicycle usage and the rapid development of dock-less app-based bicycle-sharing systems highlight the urgent need to assess the bikeability level in Chinese cities. However, this unique setup renders obsolete most of the western tools used to rank cities with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several methods and variables have been used for determining bikeability indexes. Among the most used methods, weighted regression, discrete choice, holistic approach and multi-criteria analysis using the additive or weighted linear combination method, and spatial analysis, can be highlighted [41][42][43][44][45][46].…”
Section: Bikeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods and variables have been used for determining bikeability indexes. Among the most used methods, weighted regression, discrete choice, holistic approach and multi-criteria analysis using the additive or weighted linear combination method, and spatial analysis, can be highlighted [41][42][43][44][45][46].…”
Section: Bikeabilitymentioning
confidence: 99%
“…A review of the literature identified the existence of cycling infrastructures and their characteristics (such as the presence, type and width of cycle paths, the existence of bike racks and routes sinuosity) [41,43,[45][46][47][48]; land use [42,43,47,48]; population and behavioral and social aspects [42,43,45]; safety [43][44][45] and slope [41,42,44,45,48] as the most used variables. The variables that significantly influence the index values are, in most cases, the existence of dedicated cycling infrastructure, the network characteristics and safety.…”
Section: Bikeabilitymentioning
confidence: 99%
“…To evaluate the extent to which cycling is facilitated, the notion of bikeability was created by complementing the concept of walkability. Subsequently, index systems, as instruments to quantify it, have been developed by many studies (Porter et al, 2020;Cain et al, 2018;Manton et al, 2016;Gullón et al, 2015;Koh and Wong, 2013;Horacek et al, 2012;Wahlgren et al, 2010;Hoedl et al, 2010;Clifton et al, 2007;Titze et al, 2012;Arellana et al, 2020;Winters et al, 2013;Guler and Yomralioglu, 2021;Lin and Wei, 2018;Gholamialam and Matisziw, 2019;Resch et al, 2020;Kamel et al, 2020;Grigore et al, 2019;Osama et al, 2020;Chevalier and Xu, 2020;Kang et al, 2019;Schmid-Querg et al, 2021;Galanis et al, 2018). This topic became even more relevant with the advent of bicycle-sharing systems (Du et al, 2019;Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…European countries such as the Netherlands, Norway and the United Kingdom have been already expanding bicycle lanes in the city and encouraging the use of bicycles in daily life. Chevalier and Xu (2020) summarize studies on theories and policies of these bicycle-friendly cities in western countries. Furthermore, the study focuses on how to apply those policies into Chinese context.…”
mentioning
confidence: 99%